Pengaruh Penerapan Green School Terhadap Minat Belajar Siswa di SMPN 26 Surabaya - Rahmah, Ulfatur (Universitas Nurul Jadid, 2017)
This study attempts to describe the implementation of green school program and its effect on the students’ learning motivation in Junior High School 26 Surabaya. This school is chosen since it has carried the program long time ago, and always gets more advanced lavels now rather than other around schools. By using mix research method, the study results in a finding that green school program in SMPN 26 Surabaya is well organized and gets a correlation score, using linear regression analysis, average 0.529 and level of significance 0,000. It means that green school program has positive impact on students’ learning motivation in that school